Plasmon-enhanced magneto-optical detection of single-molecule magnets. Issue 6 (10th April 2019) - Pineider, Francesco; Pedrueza-Villalmanzo, Esteban; Serri, Michele; Adamu, Addis Mekonnen; Smetanina, Evgeniya; Bonanni, Valentina; Campo, Giulio; Poggini, Lorenzo; Mannini, Matteo; de Julián Fernández, César; Sangregorio, Claudio; Gurioli, Massimo; et al.
Abstract : Single-molecule magnets in hybrid architectures with plasmonic nanoantennas exhibit significant enhancement in their magneto-optical response. Abstract : Here we report on nanoarchitectures composed of molecular magnets deposited on optical nanoantennas. We demonstrate a significantly boosted magneto-optical detection of a thin film of a terbium(iii ) bis-phthalocianinato (TbPc2 ) single-molecule magnet and we track down the origin of this enhancement to nanoantenna effects at the optical level. This finding suggests that the vast knowledge on plasmon-enhanced spectroscopies can be readily extended to magneto-optics, thus paving the way to strong magneto-optical enhancements for the readout of nanometric devices embedding single-molecule magnets.